Proceedings of the 22nd ACM Conference on Virtual Reality Software and Technology 2016
DOI: 10.1145/2993369.2996341
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability analysis in virtual reality using the HTC vive

Abstract: Postural stability is an important measure for many medical diseases such as Parkinson. In the last years, research focused on using inexpensive and portable devices to measure postural stability, while the visual targets were physical objects in the environment. Sensing balancing boards were used to measure stance forces, while movements of the upper body were not taken into account. Within this paper, postural stability was measured using the HTC Vive. A variation of a virtual fixation point's distance was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Other related work presented experiments that were performed with the use of 3D Cave projectors and polarized lenses presenting the test subjects with visualvestibulosomatosensory conflicting information [28]. Most recent work presented in [29] analyses postural stability in VR using the HTC Vive. Postural stability was measured through body sway using the tracking system provided by the HTC Vive.…”
Section: Balance and Visual Induced Motion Sickness Studies In Vrmentioning
confidence: 99%
“…Other related work presented experiments that were performed with the use of 3D Cave projectors and polarized lenses presenting the test subjects with visualvestibulosomatosensory conflicting information [28]. Most recent work presented in [29] analyses postural stability in VR using the HTC Vive. Postural stability was measured through body sway using the tracking system provided by the HTC Vive.…”
Section: Balance and Visual Induced Motion Sickness Studies In Vrmentioning
confidence: 99%
“…To induce users to become more immersed in a VR system, the system generally presents the required 3D scene information through a VR headset. At present, Oculus Rift [11,12], 3Glasses [13], and HTC Vive [14,15] are the most popular VR headsets, as shown in Figure 1. 1. Oculus Rift [11,12] Oculus Rift is a VR head-mounted display (HMD) system developed by Oculus VR.…”
Section: Vr Headsetmentioning
confidence: 99%
“…Therefore, users are not allowed to move freely to interact in fields through 3Glasses. [14,15] HTC Vive is a highly popular VR HMD at present. It is capable of utilizing the room scale technology to set the real-world room environment as a 3D interactive virtual space in which users are allowed to move freely and use a handheld controller with the motion tracking function to manipulate 3D virtual objects.…”
Section: Glasses [13]mentioning
confidence: 99%
“…Numerous studies have examined the possibility of using virtual reality for improving rehabilitation and gait (Booth et al 2013;Corbetta et al 2015;Darekar et al 2015;Palacios-Navarro et al 2016), but few studies used head-mounted displays to provide fully immersive virtual reality. Among those that have measured gait stability, all reported worsened stability when subjects used the virtual reality head-mounted display (Calogiuri et al 2017;Epure et al 2014;Kawamura and Kijima 2016;Kelly et al 2008;Lott et al 2003;Robert et al 2016;Soffel et al 2016). Two studies have found improvements in timed up-and-go performance in stroke patients when trained in virtual reality compared with conventional training (Jung et al 2012;Kang et al 2012), but the head-mounted displays for these studies were similar to spectacles placed away from the eyes, providing users with peripheral vision.…”
Section: Introductionmentioning
confidence: 99%